Retention of core melt inside kontaymenta for severe accidents of nuclear reactors - Молчанов, Игорь Александрович; Шумилин, Максим Павлович (Eastern-European Journal of Enterprise Technologies, 2012)
The analysis of the processes occurring in violation of the integrity of the reactor vessel. Studied the international experience in designing devices hold the melt. To select the optimal concept of the effective cooling of corium